Service Quality Level and Customer Satisfaction of Pharmaceutical Stores in Muar, Johor - Ruzaihan, Muhammad Izzul Hilmi; Hashim, Fazian; Eni, Sabariah; Zainal, Rozlin (Research in Management of Technology and Business, 2020)
Customer satisfaction has long been recognised as the most important element in determining the quality of services provided by an organization. This study aims to investigate the relationship between customer satisfaction and service quality level provided by pharmaceutical stores in Muar, Johor. Pharmaceutical stores’ service delivery depends much on their customer satisfaction feedback and acceptance. SERVQUAL model has been adapted for this research. The model consists of five dimensions that measure service quality; tangibility reliability, responsiveness, assurance, and empathy. Quantitative research method was applied for data collection purposes whereas questionnaire was used as the main instrument. Target respondents in this study are among customers that normally attend services provided by pharmaceutical stores. The outcome suggested the relationship between service quality level and customer satisfaction that attended services provided by pharmaceutical stores are still low in several dimension concentrating highly in the reliability element. Realiability towards the services provided, level of patient-physician relationship, caring and caring attitude toward the patient and all other elements should be improved and upgraded. In conclusion, the research help and encourage pharmaceutical stores operators in understanding more of the expectations and satisfactions of the customers.